2017
DOI: 10.3390/e19040164
|View full text |Cite
|
Sign up to set email alerts
|

Heisenberg and Entropic Uncertainty Measures for Large-Dimensional Harmonic Systems

Abstract: Abstract:The D-dimensional harmonic system (i.e., a particle moving under the action of a quadratic potential) is, together with the hydrogenic system, the main prototype of the physics of multidimensional quantum systems. In this work, we rigorously determine the leading term of the Heisenberg-like and entropy-like uncertainty measures of this system as given by the radial expectation values and the Rényi entropies, respectively, at the limit of large D. The associated multidimensional position-momentum uncer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 87 publications
1
35
0
Order By: Relevance
“…Then, uncertainty measures of entropic character [26][27][28][29][30][31][32][33][34] have been considered; they are much more appropriate because, contrary to the Heisenberg-like ones, they do not depend on any specific point of the system. Recently these studies have been extended by calculating the dominant term of the Heisenberglike and Rényi-entropy-based uncertainty measures for both the D-dimensional hydrogenic and harmonic systems at the quassiclassical border in the two conjugated position and momentum spaces [35,36]. It was found that the Heisenberg-like and Rényi-entropy-based equality-type uncertainty relations for all of the D-dimensional harmonic oscillator states in the pseudoclassical (D → ∞) limit are the same as the corresponding ones for the hydrogenic systems, despite the so different character of the oscillator and Coulomb potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Then, uncertainty measures of entropic character [26][27][28][29][30][31][32][33][34] have been considered; they are much more appropriate because, contrary to the Heisenberg-like ones, they do not depend on any specific point of the system. Recently these studies have been extended by calculating the dominant term of the Heisenberglike and Rényi-entropy-based uncertainty measures for both the D-dimensional hydrogenic and harmonic systems at the quassiclassical border in the two conjugated position and momentum spaces [35,36]. It was found that the Heisenberg-like and Rényi-entropy-based equality-type uncertainty relations for all of the D-dimensional harmonic oscillator states in the pseudoclassical (D → ∞) limit are the same as the corresponding ones for the hydrogenic systems, despite the so different character of the oscillator and Coulomb potentials.…”
Section: Introductionmentioning
confidence: 99%
“…These results extend and complement various efforts about the information entropies of harmonic systems. [11,28,29,32,[36][37][38]63,69,70,73,76,77,[84][85][86][87][88][89]…”
Section: Shannon Entropy Of High-dimensional Harmonic Systemsmentioning
confidence: 99%
“…∞ limit. Here again, to determine the dependence on the hyperquantum numbers, we have to go further in the asymptotical behavior (76) and (75) for the Laguerre and Gegenbauer functionals E 1L∞ À Á and EC ∞ , respectively, which requires a deeper research in approximation theory. These results extend and complement a number of results about the multidimensional hydrogenic systems.…”
Section: Shannon Entropy Of High-dimensional Hydrogenic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This linearization problem, which is equivalent to the evaluation of integrals of the product of three or more HOPs of the same type, is also called Clebsch-Gordan-type problem because its structure is similar to the Clebsch-Gordan series for spherical functions [8,9,40,41]. It arises in a wide range of mathematical and physical problems, from the generalized moment problems as stated by M. G. Krein [42][43][44], stochastic processes [45] and combinatorics [46][47][48][49], information entropies [20,[50][51][52][53][54] up to quantum physics. Indeed, numerous physical and chemical properties of a given complex system (atoms, molecules,...) are determined by these overlap integrals or Krein-like functionals of various HOPs, basically because the main route for the search of the solutions of the corresponding Schrödinger equation is their expansion as linear combinations of a known basis set of functions which are controlled by the HOPs (see e.g.…”
Section: Introductionmentioning
confidence: 99%